2018
DOI: 10.1123/jpah.2017-0456
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Measured Physical Activity and Sedentary Behavior: A Cross-Sectional Study of Brazilian Older Adults

Abstract: Background: To examine the level of physical activity and sedentary behavior (SB), measured with accelerometers, in older adults from a city in southern Brazil according to sociodemographic and health characteristics. Methods: The sample consisted of 425 older adults (≥63 y) from the EpiFloripa Aging Study. Light physical activity (LPA), moderate to vigorous physical activity (MVPA), and SB were measured with accelerometers over a period of 7 days. Results: The older adults spent two-thirds of the time of use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
6
11
0
1
Order By: Relevance
“…Our study found that the obese and overweight elder had a higher chance of having limitations in the ADL than the eutrophic ones, results also found by other studies (Dos Santos et al, 2018;Palacios-Ceña et al, 2012). This relationship can be explained because obesity is related to low PA on the part of obese and because excess body fat is associated with the development of CNCD (Jensen&Hsiao, 2010), contributing to the functional loss.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our study found that the obese and overweight elder had a higher chance of having limitations in the ADL than the eutrophic ones, results also found by other studies (Dos Santos et al, 2018;Palacios-Ceña et al, 2012). This relationship can be explained because obesity is related to low PA on the part of obese and because excess body fat is associated with the development of CNCD (Jensen&Hsiao, 2010), contributing to the functional loss.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study reinforce the notion that FC is determined by a wide network of socio-demographic, behavioral and health factors. As in previous studies, this study shows that women, the non-married, those with lower income (Matos et al, 2018), with lower schooling, with a higher number of diagnoses, those who take more than 5 medicines, and those inactives or insufficiently actives have a higher chance of being dependent in daily life (Ballesteros, Moreno-Montoya, 2018;dos Santos et al, 2018;Artaud et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…To address the uncertainties and subjectivity that may be present in self-reported questionnaires, some studies have used accelerometers. Indeed, recent studies have shown that the use of accelerometers in older adults to measure physical activity levels provides more reliable information [ 84 , 85 ]. However, it is difficult to use accelerometers over a long period of time [ 86 ].…”
Section: Discussionmentioning
confidence: 99%